Nuclear in Situ Hybridization of High –Risk and Low-Risk Human Papilloma Virus DNA in Tissues from a Group of Iraqi Patients with Sino Nasal and Nasopharyngeal Benign and Malignant Tumors - Saad Hasan Mohammed Ali (Journal of Global Pharma Technology, 2017)
Background: Human papilloma viruses (HPV) are well known viruses that can induce tumor genesis in proliferative epithelial tissues. Many studies implicated HPV in progression of head and neck benign and malignant tumors by affecting cell cycle proteins expression. Objectives This study was designed to determine the rates of detection high- risk HPV16/18 and low -risk HPV6/11 genotypes in tissues from nasal cavity, par nasal sinuses and nasopharyngeal lesions that include apparently healthy tissue, nasal polyps (NP), sin nasal papillomas (SNP) , nasopharyngeal carcinomas(NPC) and sin nasal carcinomas (SNC).Methods: This study is a retrospective one. Total 125formalin -fixed paraffin embedded tissue blocks including: 35 nasal polyps, 35 sin nasal papilloma S, 29 nasopharyngeal carcinomas 6 sin nasal carcinomas and nasal apparently healthy tissues. After his to pathological confirmation Viral DNA localization performed using chromomeric in situ hybridization (CISH). Results: In sin nasal papillomas and nasal polypsHPV6/11was detected in 54.3% and 22.9% respectively and in sin nasal and nasopharyngeal carcinomas (SNC+NPC) group was detected in 14.3% where the results have revealed highly significant differences (P<0.01).Percentage of HPV16/18 genotypes in SNC+NPC group was 31.4 %, in sin nasal papilloma tissues was detected in 25.7% and in nasal polyps tissues was detected in 11.4 %where such results have revealed non-significant differences (P>0.05).Conclusions: The present results point for a possible association between high on cogenic-risk HPV genotypes with sin nasal papillomas as well as SNC and NPC in the way of their pathogenesis and /or tumor genesis where as a low association was observed between high and low- risk HPV genotypes with nasal polyps lesions.Keywords: Low- riskHPV-6/11, High- riskHPV-16/18, CISH, Sino nasal and Nasopharyngeal lesions.